ASSA14-03-25 Cellular repressor of E1A-stimulated genes antagonises inflammation and promotes autophagy via lysosome biogenesis in mouse macrophages. (1st December 2014) - Sun, M; Yan, C; Tian, X; Li, Y; Tao, J; Han, Y
Abstract : Objective: Macrophage inflammation plays an important role in the pathogenesis of atherosclerosis. In this study, we investigated the involvement of cellular repressor of E1A-stimulated genes (CREG) in tumour necrosis factor-α (TNF-α)-induced macrophage inflammation, and explored its inhibitory capacity and mechanisms to assess its potential as a therapeutic reagent for atherosclerosis. Methods and results: We confirmed that CREG played an important role in TNF-α-induced macrophage inflammation and had anti-inflammatory effects in RAW 264.7 mouse macrophages induced by TNF-α, using enzyme-linked immunosorbent assays and western blotting. Gain-of-function and loss-of-function experiments revealed that CREG promoted autophagy in TNF-α-induced RAW 264.7 cells. Using the autophagy inhibitors 3-methyladenine and bafilomycin A, we demonstrated that autophagy played an important role in attenuating TNF-α-induced inflammation. Immunofluorescence analysis and western blotting showed that CREG protein stimulated the expression and maturation of cathepsin B and cathepsin L and induced the biogenesis of lysosomes, while CREG deficiency reduced lysosome biogenesis. Exogenous CREG protein was located in lysosomes, as shown by confocal microscopy and immunoprecipitation analysis. CREG protein played a critical role in the distribution but not in the expression of mannose-6-phosphate/insulin-like growth factor II receptor (M6P/IGFIIR), as demonstrated by western blotting and immunofluorescence analysis. In vivo experiments indicated that CREG protein alleviated the development of aortic atherosclerosis and affected inflammation and autophagy in aortas of ApoE −/− mice. Conclusion: CREG inhibits macrophage inflammation and promotes autophagy mediated by lysosome biogenesis, which is related to the distribution of M6P/IGFIIR. CREG may represent a new therapeutic target against atherosclerosis.